Approach to 5-substituted 6, 7, 8, 9-tetrahydro-5H-pyrido[3, 2-c]azepines. Issue 20 (17th May 2017) - Subota, Andrii I.; Artamonov, Oleksiy S.; Gorlova, Alina; Volochnyuk, Dmitriy M.; Grygorenko, Oleksandr O.
Graphical abstract: Highlights: Approach to 5-substituted 6, 7, 8, 9-tetrahydro-5 H -pyrido[3, 2- c ]azepines is reported. The products were prepared in 8 steps, in up to 10% total yield, and on up to a 10 g scale. Staudinger–aza-Wittig reaction was used for the azepane ring construction. Only products with relatively hindered groups at the C-5 position were obtained. In some cases, 5, 7, 8, 9-tetrahydrooxepino[4, 3- b ]pyridines were isolated. Abstract: An approach to 5-substituted 6, 7, 8, 9-tetrahydro-5 H -pyrido[3, 2- c ]azepines via the cyclization of 1-(2-(3-azidopropyl)pyridin-3-yl)alkanones under Staudinger–aza-Wittig reaction conditions is described. The overall reaction sequence includes eight steps and allows for the preparation of gram quantities of the title products. In some cases, the formation of 5, 7, 8, 9-tetrahydrooxepino[4, 3- b ]pyridine derivatives was observed.